The nexus between ecology of foraging and food security: cross-cultural perceptions of wild food plants in Kashmir Himalaya - Syed Waseem Gillani; Mushtaq Ahmad; Muhammad Manzoor; Muhammad Waheed; Zafar Iqbal; Riaz Ullah; Andrea Pieroni; Lixin Zhang; Naji Sulaiman; Mousaab Alrhmoun (BMC, 2024)
Abstract Background Wild food plants (WFPs) play an important role in the traditional dietary habits of various indigenous communities worldwide, particularly in mountainous regions. To understand the dynamics of food preferences, cross-cultural studies on food plants should be conducted across diverse ethnic groups in a given area. In this context, the current study investigated the use of WFPs by seven different cultural groups in the Kashmir Himalayan Region. In this area, people gather wild plants and their parts for direct consumption, traditional foods, or sale in local markets. Despite this reliance, documentation of the food system, especially concerning WFPs, is notably lacking. Hence, our research aimed to document WFPs, along with associated traditional ecological knowledge, and identify major threats to their long-term sustainability in Division Muzaffarabad. Methods Through a comprehensive approach involving questionnaires, interviews, focus groups, and market surveys, we gathered data from 321 respondents. PCA was performed to analyze threats and plant use using "factoextra" in R software. Origin Pro was used to create a chord diagram, while R software was used to generate a Polar heat map. Additionally, a Venn diagram was created using Bioinformatics software. Results The study included 321 informants, of whom 75.38% were men and 24.61% were women. In total, 113 plant taxa from 74 genera and 41 botanical families were reported. Polygonaceae and Rosaceae accounted for the majority (17 species each), followed by Lamiaceae (7 species). Leaves were the most used part as food sources (41.04%), followed by fruits (33.33%). Most of the species are consumed as cooked (46.46%) and as raw snacks (37.80%). A total of 47 plant species were collected and cooked as wild vegetables, followed by 40 species used as fruits. This study is the first to describe the market potential and ecological distribution of WFPs in the study area. Cross-comparison showed that utilization of WFPs varies significantly across the region and communities, including their edible parts and mode of consumption. Jaccard index (JI) value ranged from 5.81 to 25. Furthermore, the current study describes 29 WFPs and 10 traditional food dishes that have rarely been documented in Pakistan's ethnobotanical literature. Climate change, invasive species, expansion of agriculture, and plant diseases are some of the most significant threats to WFPs in the study area. Conclusions The older age group has more knowledge about WFPs compared to the younger generation, who are not interested in learning about the utilization of WFPs. This lack of interest in information about WFPs among the younger generation can be attributed to their limited access to markets and availability of food plants in the study area. Traditional gathering of food plants has been reduced in younger generations during recent years; therefore, it is crucial to develop effective conservation strategies. These efforts not only safeguard indigenous flora, food knowledge, and cultural heritage, but they also contribute to food security and public health by utilizing local wild foods in the examined area.